The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jorganchem.2017.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Te-Te and C-Te bond cleavage in the oxidative addition of diaryl and dialkyl ditellurides to Pt(0) centers

Abstract: † Electronic Supplementary Information (ESI) available: Crystal data and details of structure determination and selected bond parameters of 2-5, CCDC 1522462-1522465, Definition of the angle of distortion. Energy profile of Th2Te2 + [Pt((h 2nb)(dppn)]. 31 P{ 1 H} NMR spectrum of [Pt(TeTh)2(dppn)].The oxidative addition reaction of ditellurides R2Te2 [R = n Bu, Ph, Th (2-thienyl, C4H3S)] to [Pt(η 2 -nb)(dppn)] (nb = norbornene, dppn = 1,2-bis(diphenylphosphino)naphthalene) was found to afford [Pt(TeR)2(dppn)] [… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 51 publications
1
4
0
Order By: Relevance
“…For most of the structural parameters, a linear dependence with the size of the chalcogen or the size of the metal is observed along the series [M(L S )(PPh 3 )] – [M(L Se )(PPh 3 )] – [M(L Te )(PPh 3 )]. The Pd1–Te1 and Pt1–Te1 bonds of 2.4825(2) and 2.502(1) Å are similar to the shortest bond lengths reported in previous studies of palladium [ 21,25–29,34,36–38 ] and platinum [ 39–52 ] phenyltellurolato complexes. Remarkably and probably as a result of the strain in the five‐membered Te1–Ni1–N1 chelate ring, the Ni1–Te1 bond length in [Ni(L Te )(PPh 3 )] is only 2.4050(5) Å.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…For most of the structural parameters, a linear dependence with the size of the chalcogen or the size of the metal is observed along the series [M(L S )(PPh 3 )] – [M(L Se )(PPh 3 )] – [M(L Te )(PPh 3 )]. The Pd1–Te1 and Pt1–Te1 bonds of 2.4825(2) and 2.502(1) Å are similar to the shortest bond lengths reported in previous studies of palladium [ 21,25–29,34,36–38 ] and platinum [ 39–52 ] phenyltellurolato complexes. Remarkably and probably as a result of the strain in the five‐membered Te1–Ni1–N1 chelate ring, the Ni1–Te1 bond length in [Ni(L Te )(PPh 3 )] is only 2.4050(5) Å.…”
Section: Resultssupporting
confidence: 85%
“…Selected bond lengths [Å] and angles (°) in the dichalcogenides {HL Y } 2 [30] and their nickel, palladium and platinum complexes [M(L Y )(PPh 3 )] (Y = Se, Te). [21,[25][26][27][28][29]34,[36][37][38] and platinum [39][40][41][42][43][44][45][46][47][48][49][50][51][52] [53] Ni(TeMes)Cp(PEt 3 ), [54] [W(CO) 5 -μ-(TePh)NiCp(PPh 3 )] [55] and [57] [(NiCpiPr 4 ) 2 -μ-( Te) 2 ] (2.44-2.45 Å), [58] [CpFe(C 5 H 4 )-Te(I) 2 -Ni(NHC)Cp] (2.4407(8) Å) [59] and (μ 4 -telluro)-hexakis(μ 3 -telluro)bis(μ 2 -bis(diphenylphosphino)methane)-bis(η 5 -tert-butylcyclopentadienyl)-pentanickeldiniobium (2.436(5) Å) [60] show the overall shortest Ni-Te bond lengths. (m/z = 538.0818) can be observed.…”
Section: Introductionmentioning
confidence: 99%
“…It is possible that the proposed one-electron decomposition routes of the didodecyl ditelluride reagent on the metal cations facilitate this type of bonding by selectively breaking the C–Te bonds of the ditellurides. While intermediates from oxidation addition of ditellurides on M(0) complexes have been captured and identified, we are unaware of any captured intermediates of reactions of ditellurides on M­(II) and M­(III) complexes.…”
Section: Resultsmentioning
confidence: 99%
“…In two monoclinic [Pt{η 2 -Ph 2 P(CH 2 ) 2 PPh 2 }(TePh) 2 ] (at 120 K) and [Pt{η 2 -Ph 2 P(CH 2 ) 2 PPh 2 }{Te(C 4 H 3 S)} 2 ] (at 120 K) (Risto et al, 2007) each Ph 2 P(CH 2 ) 2 PPh 2 forms a five-membered metallocyclic ring with the mean value of 86.6° (PC 2 P). In another three complexes: orthorhombic [Pt {η 2 -Ph 2 P(CH 2 ) 3 PPh 2 }{Te(mes)} 2 ]‧3C 6 H 6 (at 100 K) (Chauhan et al, 2013), monoclinic [Pt{η 2 -Ph 2 P(C 10 H 6 )PPh 2 }{Te(Ph)} 2 ]‧ 3toluene (at 133 K), and triclinic [Pt{η 2 -Ph 2 P(C 10 H 6 ) PPh 2 }{Te(C 4 H 3 S)} 2 ] (at 133 K) (Karjalainen et al, 2017) each of the bidentate-P,P-donor ligand creates sixmembered metallocyclic ring with the mean value of P-Pt-P bite angle of 91.2° (PC 3 P). Structure of [Pt {η 2 -Ph 2 P(C 10 H 6 )PPh 2 }{Te(C 4 H 3 S)} 2 ] (Karjalainen et al, 2017) is shown in Figure 3 as an example.…”
Section: Cis-pt(η 2 -P 2 L)(tel) 2 Derivativesmentioning
confidence: 99%